Increased productivity and technical efficiency of rice farming with the System of Rice Intensification (SRI) method in Purworejo District, Central Java - Herry Maridjo; Y MV Mudayen; A Tri Prihantoro (Universitas Hayam Wuruk Perbanas, 2016)
This study aims to determine whether there is a significant difference in productivity between organic and inorganic rice farming, whether there is a significant difference in technical efficiency between organic nd inorganic rice farming, and whether fertilizer costs, labor costs, arable land area, and the length of the use of System of Rice Intensification (SRI) have a significant effect on the organic rice production. The target of this research is the improvement of economic efficiency and organic rice farming productivity in Purworejo District, Central Java. To achieve this target, this study used SRI method. The population was all farmers of inorganic and organic rice farming in Purworejo District. The samples consist of 45 people from organic rice farmers and 45 people from inorganic rice farmers in Ringgit Village, Purworejo. They were collected by random sampling and the data were analyzed using descriptive analysis and quantitative analysis. Descriptive analysis was done by comparing all necesary activities in both organic and inorganic rice farming. The descriptive analysis concludes that there is a difference in terms of the selection of seeds, seedlings, seed treatment before sowing, planting and watering, fertilizing, weeding and pest control. Quantitative analysis is done using Analysis of Variance (ANOVA) and multiple linear regeresi. The quantitative analysis concludes that there is a significant difference in productivity between organic rice farming and inorganic rice farming. There is a significant difference in technical efficiency between organic rice farming and inorganic rice farming. Fertilizer costs, labor costs, arable land area, and the length of the use of SRI method have a significant effect on the organic rice production.